REVITALISASI ENTREPRENEURSHIP DALAM MEMBANGUN PEREKONOMIAN UMAT - Nursanjaya Nursanjaya (Program Studi Administrasi Bisnis, 2020)
National economic development, apart from bringing positive economic growth among the ummah, also creates socio-economic disparities between large, medium and small entrepreneurs. This situation is certainly not good for the Islam community in particular and the Indonesian nation. So the revival and progress of the Muslim economy must be a supporting factor for the revitalization of entrepreneurship in building the economy of the Ummah. For this reason, a solution to the economic system is needed that is further away from the true essence of justice. The emergence of various innovations in the world of entrepreneurship in the field of sharia-based economics, the formation of a network of Islamic economic institutions, the implementation of various human resource development trainings to produce reliable and professional entrepreneurs but not to lose their faith and national identity, are dreams and aspirations to revitalize entrepreneurship in building the economy of the people.